Case reports: hypovitaminosis A coupled to epilepsy in four calves - Issi, M.; Gul, Y. (Ecole Nationale Veterinaire Toulouse, 2010)
In this study, four calves were brought to clinic for a history of epileptic attacks. Throughout general clinical examination, several clinical signs characteristics of vitamin A deficiency (moving difficulties, ocular globe modifications, beautiful blindness, loss of palpebral and pupillary reflexes) were evidenced in the 4 animals. A high pressure (> 200 mm H(2)O) of the cerebrospinal fluid (whose the physical aspect, cellularity and protein concentrations were normal) was found in 2 animals. In all calves, deeply lowered serum vitamin A and beta-carotene concentrations (< 70 mu g/L and < 100 mu g/L respectively) confirmed the diagnosis of hypovitaminosis A. Expected the case n degrees 4 infested with ascarids, the others were not parasited. After oral treatment with vitamin preparation (Ademin (R) containing vitamins A, D(3) and E) for 2 days, no epileptic attack occurred in any animal and the other symptoms, especially ocular signs, gradually disappeared within a week. These cases confirm that vitamin A deficiency may induce epileptic attacks in calf and that a vitamin supplementation at an early stage may totally cure affected animals.
Keywords: Calf; epilepsy; blindness; cerebrospinal fluid; hypovitaminosis A